Pertimbangan Hakim Dalam Menjatuhkan Putusan Perkara Perjanjian Pinjam Pakai Tanah Pusako Tinggi Yang Belum Bersertifikat (Studi Putusan Perkara Nomor 34/Pdt.G/2021/PN.Pdg) - Mardius Mardius; Messi Veryani Suci (Normative Jurnal Ilmiah Hukum, 2025)
Article 1754 of the Civil Code loan agreement is an agreement by which one party gives to another party, The purpose of the study is 1) To determine the Judge's Consideration in making a decision on a loan agreement for high-ranking land that has not been certified in Case Decision Number 34.Pdt.G/2021/PN.Pdg. 2) To determine the Analysis of Case Decision Number 34/Pdt.G/2021/PN.Pdg in making a decision on a loan agreement for high-ranking land that has not been certified. The benefits of the study are theoretical and practical benefits. The research method is normative law and the data source is secondary data. Data collection techniques are document studies and literature studies. Data processing is editing and coding. The analysis technique is qualitative. The results of the study, first: The Judge's consideration in resolving land disputes in the decision of case Number 34/Pdt.G/2021/PN.Pdg can be concluded that because it has been legally and proven that Defendants A and B without permission from the Plaintiff built a house with a total of 23 units and 4 graves on the Defendant's Pusako Land and Defendants A and B could not prove their answers, then in the opinion of the Panel of Judges, Defendants A and B's exceptions were rejected in their entirety. Analysis of the Decision of Case Number 34/Pdt.G/2021/PN. Pdg in passing a decision on the case of a loan agreement for high pusako land that has not been certified, namely that the decision has legal force and is binding on both parties.